(untitled) (IAHS Medical Journal, 2023)
Background: Surgical Site Infections (SSI) increase costs, hospital stay, morbidity, and mortality. Vacuum-Assisted Closures (VAC) system has been gaining popularity recently in managing wounds to reduce SSI. But the current guidelines do not recommend its routine use for surgical wounds. This study aimed to compare the effectiveness and safety of VAC with conventional wound closure techniques for preventing SSIs in the major contaminated surgical wound. Methods and materials: Sixty patients with a contaminated surgical wound from the Department of Surgery and Department of Casualty of Chittagong Medical College Hospital were randomized in a 1:1 ratio to receive either VAC (Using Romovac device) or conventional wound closure. The primary endpoint was the rate of uncomplicated wound healing, defined as a Southampton wound score of <2 at 30 days postoperatively. Secondary outcomes include duration of hospital stay and other complications (Defined by the Clavien-Dindo Classification). The primary analysis was an intention-to-treat analysis performed with a Chi-square test. Results: There were no significant differences in mean age, sex, body mass index, smoking history, wound class, indication for surgery and duration of surgery between the two groups. At 30 days postoperatively, 29 (96.3%) of 30 patients undergoing VAC had uncomplicated wound healing compared to 13 (43.6%) in the conventional closure group (p<0.001). Most patients (26/30, 86.6 %) in the VAC group experienced Clavien-Dindo grade I or II complications. In contrast, in the conventional closure group, 28 (93.3%) patients developed Clavien-Dindo Grade III or IV complications (p<0.001). The mean length of hospital stay was significantly shorter in the VAC group than in the conventional closure group (12.2±3.59 versus 29.07±10.36 days, p<0.001). Conclusion: VAC resulted in favourable wound healing with less complication and shorter hospital stay than the conventional technique for the closure of the contaminated surgical wound. IAHS Medical Journal Vol 5(2), Dec 2022; 6-10